2021
DOI: 10.3390/ijms22158118
|View full text |Cite
|
Sign up to set email alerts
|

Copresence of High-Risk Human Papillomaviruses and Epstein–Barr Virus in Colorectal Cancer: A Tissue Microarray and Molecular Study from Lebanon

Abstract: Colorectal cancer (CRC) is the third most common cause of cancer-related deaths worldwide. Human papillomaviruses (HPVs) and Epstein–Barr virus (EBV) have been reported to be present in different types of human cancers, including CRCs, where they can play a key role in the onset and/or progression of these cancers. Thus, we herein explored the prevalence of high-risk HPVs and EBV in a cohort of 94 CRC tissue samples and 13 colorectal normal tissues from the Lebanese population using polymerase chain reaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 95 publications
7
6
0
Order By: Relevance
“…Moreover, since our study reports a fairly low prevalence of HPV 16 (4%) infections in the Qatari CRC population, the absence of HPV reported by Khabaz [ 45 ] may be due to the use of detection methods that were based on detecting only HPV 16 and HPV 18 infections, which may be low-occurring in the GCC region. Further, in the larger MENA region, a higher prevalence of HPV in CRC was noted in Syria (54%) [ 32 ] and Lebanon (64%) [ 50 ], which is comparable to the results from our study. Interestingly, the highest prevalence of HPV in CRC in the MENA region comes from Turkey, where studies reported 81% [ 51 ] and 82% [ 52 ] of CRC samples to have HPV infections.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, since our study reports a fairly low prevalence of HPV 16 (4%) infections in the Qatari CRC population, the absence of HPV reported by Khabaz [ 45 ] may be due to the use of detection methods that were based on detecting only HPV 16 and HPV 18 infections, which may be low-occurring in the GCC region. Further, in the larger MENA region, a higher prevalence of HPV in CRC was noted in Syria (54%) [ 32 ] and Lebanon (64%) [ 50 ], which is comparable to the results from our study. Interestingly, the highest prevalence of HPV in CRC in the MENA region comes from Turkey, where studies reported 81% [ 51 ] and 82% [ 52 ] of CRC samples to have HPV infections.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, the reported data relied on a single methodology (PCR assay for all three viruses). Nevertheless, our previous studies exploring the presence of HPV and EBV in different types of cancers using PCR and IHC generated comparable results [ 19 , 34 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 87%
“…In Lebanon, our group reported HPV prevalence in 60 cases out of the 94 CRC samples (64%), with HPV-16 and HPV-18 as the most frequent HR-HPV subtypes [17].…”
Section: In Levant Countriesmentioning
confidence: 85%
“…On the other hand, high-risk HPVs (types -16, -18, -31, -33, -35, -39, -45, -51, -52, -55, -56, -58, -59, -68, -73, -82, and -83) have oncogenic potential and are associated with the development of human cancers [9]; HPV 16 and HPV18 are frequently present in cervical cancer where more than 96% of these cancers are positive for these viruses [14,15]. Subsequently, high-risk HPVs are shown to be involved in a subset of other genital cancers in addition to head and neck, colorectal, and breast cancers [16][17][18][19][20]. Several studies investigated the presence of HPVs in cancer and found the presence of high-risk HPVs correlated with vascular invasion, lymph node metastasis, and tumor grade and size [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%